THE IMPACT OF ANKLE-FOOT ORTHOSES ON BALANCE IN OLDER ADULTS: A SCOPING REVIEW - Jenna Laidler (Canadian Prosthetics & Orthotics Journal, 2021)
BACKGROUND: Balance impairment is a contributing factor to falls. Falls are a leading cause of injury and death in older adults. An ankle-foot orthosis (AFO) is a device that can be prescribed as an intervention to help individuals with compromised balance to ambulate safely.